Amyloid-Beta Related Angiitis of the Central Nervous System: Case Report and Topic Review - Nouh, Amre; Borys, Ewa; Gierut, Angelica; Biller, Jose (Frontiers in Neurology, 2014)
Amyloid-beta related angiitis (ABRA) of the central nervous system (CNS) is a rare disorder with overlapping features of primary angiits of the CNS (PACNS) and cerebral amyloid angiopathy (CAA). We evaluated a 74-year-old man with intermittent left sided weakness and MRI findings of leptomeningeal enhancement, vasogenic edema and subcortical white matter disease proven to have ABRA. We discuss clinicopathological features and review the topic of ABRA.